Effects of Anions and Surface Structure on Pt Single Crystal Dissolution in Acidic Electrolytes - Briega-Martos, Valentín; Fuchs, Timo; Drnec, Jakub; Magnussen, Olaf M.; Cherevko, Serhiy (ChemElectroChem, 2024)
Understanding the mechanisms of Pt dissolution with well-defined surfaces is vital for developing stable catalysts for electrochemical energy conversion devices such as fuel cells. This work investigates Pt dissolution from low-index single crystals in perchlorate, sulfate, and methanesulfonate acid solutions by on-line inductively coupled plasma mass spectrometry (ICP-MS), and the results are correlated with surface X-ray diffraction (SXRD) studies. The previously reported stability trend Pt(111)>Pt(100)>Pt(110) in HClO4 was confirmed for the other acids. The application of electrochemical protocols up to high potential values demonstrated that dissolution for Pt(100) increases to a lower extent than for the other planes. Dissolution is affected by the nature of the anion, especially for Pt(111), with the dissolution rate increasing in the order H2SO4>MSA>HClO4. This influence could be due to the interaction strength of the anion with Pt and its complexing ability or different ratios of the surface coverage of different oxide species. For Pt(111), SXRD measurements show different onset potentials for extraction in HClO4 and H2SO4, which can influence the dissolution processes. These results demonstrate that fundamental studies are necessary to improve the current knowledge about Pt dissolution and how to hinder it to a practical extent.
CRIS-Team Scopus Importer:2024-01-26
Keywords: dissolution; electrochemistry; mass spectrometry; platinum; single crystals